Her father's house - Plain, Belva (New York : Delacorte Press, 2002)
Decades after her father kidnapped her from his ex-wife's home to save her from an unstable environment, a young woman struggles to come to terms with her father's criminal action and the deception that forms the foundation of her entire life.
Keywords: Fathers and daughters; Young women; New York (N.Y.); Historical fiction; Domestic fiction